Gifting a Healing Education Through Writing Life and Art: A Paris Studio Residency - Jordan, Nané; Bickel, Barbara (Journal of the Canadian Association for Curriculum Studies, 2021)
We are two Canadian arts-based educational researchers who collaborated during a studio residency in Paris, France, during May 2015, for ten days. Our residency curriculum included study of feminist poet-thinker Hélène Cixous, taking walks in Paris locales, viewing women’s art, and engaging arts-based inquiry methods such as journaling, life writing and creative embodied practices, as a way to pay attention to and document our daily experiences. We practiced what we call companion pedagogy, with a feminist focus on mothering and gifting relations. We find that arts-based, restorative practices strengthen our wellbeing and resiliency as educators, and also support our desire for a more nurturing, mothering humanity to come forward for gifting a healing education. Healing education begs the question of how to address the resiliency of educators over time through what are increasingly challenging and depleting conditions of institutional cultures and economies. We thus offer creative practices such as studio residencies for collective care and gifting that can nurture a restorative pacing of life, while supporting the resiliency of educators to gift their energies towards creative curriculum visioning and enacting of social change.